Comportamiento a flexión de elementos de concreto reforzados con barras de GFRP - Buitrago Parra, Braian Rául (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
Engineering in the context of innovation, improvement and efficient use of resources, has always been in search of new materials that can be used in the construction of all types of structures, this is how before the middle of the 20th century arises the investigation of composite materials with polymeric resins and glass fibers in the aviation industry, developing a light material, with great resistance to tension and with a great advantage over steel, its high resistance to corrosion. Considering the previous properties of this new material, civil engineering began to study the behavior of fiber-reinforced polymer bars as the internal reinforcement of concrete, emerging as an alternative material to conventional steel. This is how various design codes have been created for the use of fiberglass and carbon reinforced polymer bars (GFRP and CFRP) as concrete reinforcement, one of them was developed through committee 440 of the ACI (American Concrete Institute), the document ACI 440.1 R 15 Guide for the Design And Construction of Structural Concrete Reinforced With Fiber Polymer (FRP) Bars (2015,1), which stipulates the methodology to be used for designs by limit states of resistance and service. In the Colombian Construction Regulations for Earthquake Resistant NSR-10, in title C, the design of concrete structural elements, internally reinforced with steel bars, is specified. This title is based on ACI 318; Currently the ACI is working on a parallel regulation, where internally reinforced concrete with FRP bars is considered, therefore, given the importance of being at the forefront of the latest technologies, the present investigation of concrete elements subjected to bending is carried out , typical of building mezzanines, internally reinforced with GFRP bars in order to evaluate their response to service and ultimate design loads, common in mezzanine systems in the Colombian environment. The project involved the design and construction of four slabs 4,0 m long, 0,20 m thick and 1,0 m wide, varying the amount of reinforcement to consider designs under-reinforced, over-reinforced and with amounts similar to balanced, meeting the required resistance capacity and the admissible deflections imposed by the NSR-10. Likewise, an element in concrete reinforced with conventional steel was built entirely designed under the considerations of the Colombian standard, which would serve as a point of comparison. These elements were built and tested at the Escuela Colombiana de Ingeniería "Julio Garavito", taking advantage of the existing infrastructure of the materials laboratory. The tests were carried out by modeling a bending load condition through the application of point loads on the thirds of the elements, thus creating one pure bending zone and two bending-shear zones. The tests, through the appropriate instrumentation, allowed acquiring data on ultimate capacity, deflections, efforts in the reinforcing bars and failure mode for each element. The results evidenced for each element allowed establishing relationships between theoretical and experimental capacities, discrepancies in failure modes and their possible causes, differences between theoretical and experimental deflections, as well as generating conclusions and recommendations for the design of elements reinforced with GFRP bars.
Keywords: Concreto reforzado; Comportamiento a flexión; Barras de GFRP; Construcción - tipo de estructuras; Reinforced concrete; Bending behavior; GFRP bars; Construction - type of structures